A Review of Carbon‐Supported Nonprecious Metals as Energy‐Related Electrocatalysts. Issue 10 (2nd September 2020) - Wang, Jian; Kim, Juwon; Choi, Subin; Wang, Hongsheng; Lim, Jongwoo
Abstract: The development of sustainable energy conversion and storage devices, such as fuel cells, metal–air batteries, and electrolyzers is highly dependent on the catalytic oxygen reduction reaction (ORR), oxygen evolution reaction (OER), hydrogen evolution reaction (HER), and carbon dioxide reduction reaction (CO2 RR). Carbon‐supported nonprecious metals (C@NPMs) with variable metal sizes (single atom, cluster, and nanoparticle) are attracting significant interest for catalyzing these reactions. Therefore, a systematic summary of the recent advances in this field is necessary; however, C@NPMs have seldom been comprehensively reviewed. Herein, the most recent progress (in the years 2015–2020) of C@NPMs for ORR/OER/HER/CO2 RR catalysis are reviewed. The review begins with the introduction of various synthesis methods for C@NPMs. Next, promising design strategies to modulate the electrochemical properties of C@NPMs are elaborated, including defect engineering, porosity fabrication, metal size modulation, carbon shell tuning, and multimetal coupling. Subsequently, the recent advances in C@NPMs for ORR, OER, HER, and CO2 RR catalysis are analyzed, covering the fundamentals (elemental steps, performance metrics, and catalytic mechanisms) of these reactions. This review not only analyzes the progress in the field but also conveys methods and provides insights, which can guide the future development and practical applications of C@NPMs. Abstract : This work systematically reviews the most recent progress of carbon‐supported nonprecious metals spanning multisizes (single atom, cluster, and nanoparticle) for various energy‐related electrochemical reactions, including oxygen reduction reaction, oxygen evolution reaction, hydrogen evolution reaction, and carbon dioxide reduction reaction.